Material lúdico para matemáticas - Véliz Jiménez, Cinthya Maricela (2016)
The aim of this project is to implement new teaching, playful material in order to improve the teaching process of Mathemathics in the sixth and seventh grades of Primary School at the coeducational school "John F. Kennedy". As the research carried out has proven the deficiency of the current teaching resources, this research work will improve the students' academic level, the investigation methods chosen were: Analytic-Synthetic, as well as research resources and techniques, modeling, empirical methods such as the interview, the survey and the analysis of results, this project will suppose a great contribution to change today's education based on the use of teaching resources according to today's science and therefore it will be of great importance to its target students, teachers and parents, as it will ease the teaching-learning process of Mathematics.